2020
DOI: 10.21203/rs.2.23618/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-nucleotide polymorphism rs17548629 in RIPK1 gene may be associated with lung cancer in a young and middle-aged Han Chinese population

Abstract: Background Genetic biomarkers of lung cancer (LC) susceptibility may provide a basis for treatment and prevention. This study analyzed an association between SNPs (single nucleotide polymorphisms) in the complementary region of the 3′-UTR (3' untranslated region) of microRNAs of the gene RIPK1 (receptor-interacting serine/threonine-protein kinase 1) and LC among an adult Han Chinese population aged younger than 60 years. Also explored the effect of regulation of the RIPK1 gene via rs17548629 and microRNA-1197 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Our results suggested that there was correlation between rs1642742 and metastasis and the allele A might be associated with tumor metastasis. Of course, the correlation between SNP and tumor metastasis had been reported in previous literatures, including lung cancer, breast cancer, gastric cancer, prostate cancer, and so on [42–45] . Rs1642742 is residing in the 3′UTR of the VHL , which plays an important role in mRNA translocation, stability and translational regulation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our results suggested that there was correlation between rs1642742 and metastasis and the allele A might be associated with tumor metastasis. Of course, the correlation between SNP and tumor metastasis had been reported in previous literatures, including lung cancer, breast cancer, gastric cancer, prostate cancer, and so on [42–45] . Rs1642742 is residing in the 3′UTR of the VHL , which plays an important role in mRNA translocation, stability and translational regulation.…”
Section: Discussionmentioning
confidence: 86%
“…Of course, the correlation between SNP and tumor metastasis had been reported in previous literatures, including lung cancer, breast cancer, gastric cancer, prostate cancer, and so on. [42][43][44][45] Rs1642742 is residing in the 3 0 UTR of the VHL, which plays an important role in mRNA translocation, stability and translational regulation. The variant allele of rs1642742 may affect the ability of miRNA to bind to its sequence, which in turn affects the VHL gene expression and may lead to tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis is a new programmed form of necrotic cells different from apoptosis, and anti-tumor immunity enhancement mediated by CD8 + leukocytes upon RIPK1 and RIPK3 activation in the tumor microenvironment (TME) comprises its main mechanism. Meanwhile, necroptosis can accelerate the apoptosis and necrosis of malignant tumor cells by producing immunosuppressive TME through CXCL1 and Mincle, which suggests necroptosis to be a potential immunotherapeutic target against malignant tumors (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%